Gene and protein sequences of adenovirus protein VII, a hybrid basic chromosomal protein. - Sung, M T (1983)
The sequences of both the gene and the corresponding protein of adenovirus major core protein VII have been determined. The precise location of this gene is between 43.37 and 44.90 map coordinates on the viral genome. Protein VII is 173 residues long and has a molecular weight of 19,258. Detailed analysis of its sequence has revealed four basic domains separated by several predicted alpha helices. It is proposed that intrachain folding of protein VII is driven by hydrophobic interactions of the alpha helices, leaving the basic domains of the protein to interact with DNA phosphates. Protein monomers may further associate with each other in the formation of hexameric nucleosome-like particles. The displacement and replacement of protein VII during the viral infectious cycle in the host cell appears to mimic the biology of nucleoprotamine during the processes of spermatogenesis and fertilization. The presence of a protamine-like domain affirms a hybrid histone/protamine molecular structure for protein VII, although it may resemble the protamine in function.